Impact of procurement category management on supply chain performance - Saliah, Sadhik Mohamed (2024)
Fostering supply chain resilience and sustainability is crucial for India's industries, however, traditional procurement practices often impede efficiency. Although procurement category management (PCM) practices are effective, its impact on supply chain performance (SCP) in Indian companies remains uncertain. This study aims to investigate PCM practices and their influence on SCP in Indian companies. It proposes an empirical research model designed to enhance SCP in non-financial industrial sectors, with a focus on organization strategic capability (OSC). OSC acts as a mediator in the relationship between PCM and SCP. Furthermore, this study considered eight PCM practices, two OSC measures, and three SCP measures. Four main hypotheses were developed to test the interrelationships between PCM, OSC and SCP. The study was a cross-sectional study, employing the survey methodology, conducted in India. The data obtained from 389 returned questionnaires was analyzed using structural equation modeling (SEM). The results of the SEM analyses indicated that measures of PCM were positively and highly correlated among themselves, thus suggesting that the measures were interdependent. Meanwhile, the relationship findings support that PCM has significant positive impacts on both OSC and SCP. In other words, PCM improves SCP both directly and indirectly through OSC as the mediator. In conclusion, this empirical study provides insights into the interrelationships between PCM, OSC, and SCP. The distinctiveness of this study is that the performance was higher when PCM mediated through OSC. Finally, this study recommends adoption of comprehensive PCM practices are essential to enhance the overall SCP, stressed the importance of OSC’s contribution to the supply chain professionals and policy makers across Indian industrial sectors.